Structured illumination microscopy using random intensity incoherent reflectance - Hoffman, Zachary R; DiMarzio, Charles A (Journal of biomedical optics, 2013)
Depth information is resolved from thick specimens using a modification of structured illumination. By projecting a random projection pattern with varied spatial frequencies that is rotated while capturing images, sectioning can be performed using an incoherent light source in reflectance only. This provides a low-cost solution to obtaining information similar to that produced in confocal microscopy and other methods of structured illumination, without the requirement of complex or elaborate equipment, coherent light sources, or fluorescence. The broad line width of the light emitting diode minimizes artifacts associated with speckle from the laser while also increasing the safety of the instrument. Single diffusers and cascaded diffusers are compared to provide the most efficient method for sectioning at depth. By using reflectance only, in vivo images are produced on a human subject, generating high-contrast images and providing depth information about subsurface objects.